2015
DOI: 10.1016/j.jconrel.2015.05.270
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced paracellular transport of insulin can be achieved via transient induction of myosin light chain phosphorylation

Abstract: The intestinal epithelium functions to effectively restrict the causal uptake of luminal contents but has been demonstrated to transiently increase paracellular permeability properties to provide an additional entry route for dietary macromolecules. We have examined a method to emulate this endogenous mechanism as a means of enhancing the oral uptake of insulin. Two sets of stable Permeant Inhibitor of Phosphatase (PIP) peptides were rationally designed to stimulate phosphorylation of intracellular epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 45 publications
3
44
0
Order By: Relevance
“…However, the importance of the presence of the CPP for exocytosis or direct translocation across the basolateral membrane subsequent to cellular internalization via the apical side of the plasma membrane is not known. In addition, paracellular delivery across the epithelium or endothelium may contribute to the net delivery of the cargo by directly affecting the opening and closure of the TJs via local high CPP concentrations [ 89 ] or indirectly through the binding to intracellular targets regulating the TJ dynamics [ 14 ].…”
Section: Mechanisms Of Membrane Permeation Of Cell-penetrating Pepmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the importance of the presence of the CPP for exocytosis or direct translocation across the basolateral membrane subsequent to cellular internalization via the apical side of the plasma membrane is not known. In addition, paracellular delivery across the epithelium or endothelium may contribute to the net delivery of the cargo by directly affecting the opening and closure of the TJs via local high CPP concentrations [ 89 ] or indirectly through the binding to intracellular targets regulating the TJ dynamics [ 14 ].…”
Section: Mechanisms Of Membrane Permeation Of Cell-penetrating Pepmentioning
confidence: 99%
“…In addition to their application as inert vectors for delivery of cargo molecules, an emerging concept is the dual-acting CPPs, which are both membrane permeating and bioactive. Within this context, studies have demonstrated that, in addition to being cell-penetrating, selected CPPs are able to safely modulate the intestinal paracellular barrier [ 14 , 15 ], to act as neuroprotectants [ 16 ], to or induce apoptosis in cancer cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin co-administered with PIP peptide 250 or 640 reduced blood glucose levels by 50%, respectively, after intraluminal intestinal injection in an in vivo assay using male Wistar rats. Cy3-labeled insulin was detected predominantly in the paracellular route after intraluminal intestinal injection with PIP peptide 640 [36]. Structurally, both PIP peptides 250 and 640 belong to CPPs due to their arginine-rich cationic charge.…”
Section: Transepithelial Insulin Delivery Mechanisms Through the Tranmentioning
confidence: 99%
“…However, no targeting ligands have been identified to increase paracellular transport in vivo . Recently, peptides were designed to reversibly open tight junctions of polarized intestinal epithelial cells [35, 37]. It is though that targeting with these peptides may increase paracellular transport activity.…”
Section: Trends In Actively Targeted Nanomedicinesmentioning
confidence: 99%